Phenylethynylcobalamin: A Light‐Stable and Thermolysis‐Resistant Organometallic Vitamin B12 Derivative Prepared by Radical Synthesis1. Issue 43 (12th September 2013) - Ruetz, Markus; Salchner, Robert; Wurst, Klaus; Fedosov, Sergey; Kräutler, Bernhard
<x xml:space="preserve">Abstract</x> Don't take this antivitamin! 2‐Phenylethynylcobalamin (see picture) was prepared in a newly developed radical reaction using cob(II)alamin and 1‐iodo‐2‐phenylethyne. It has an exceptionally short organometallic bond and is a remarkably light‐stable and heat‐resistant organometallic cobalamin. It is bound well by two important proteins of the human B12 transport system and has properties that are as expected for a new type of an "antivitamin B12".<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>